Butyric acid from probiotic staphylococcus epidermidis in the skin microbiome down-regulates the ultraviolet-induced pro-inflammatory IL-6 cytokine via short-chain fatty acid receptor - Keshari, S. (MDPI AG, 2021)
10.3390/ijms20184477